The Oath Concept: Basis for Dismissal from Office “for Breach of Oath” and System of Guarantees for Labor Rights Protection - Khlystun, Yuliia (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2024)
The specified article studies the oath concepts, “breach of oath”, and the dismissal of a special subject — a judge — on this basis. It emphasizes the importance of ensuring that the norms governing the procedure and process of dismissal from office are effective, taking into account high standards imposed on judges (both in their appointment to the office and in the administration of justice), and should serve as a reliable safeguard against wrongful dismissals. Each stage of a disciplinary proceeding involving a judge must uphold labor guarantees of rights security that cannot be violated. The paper summarizes that dismissal from office should take place considering the provisions of the Labor Code of Ukraine, along with the norms of special legislation defining the status of a judge. In addition, there should be an effective system of guarantees for the protection of labor rights, which should operate in today’s conditions.
Keywords: Oath, oath text, judge dismissal, breach of oath, guarantees of labor rights protection, disciplinary proceeding